Association between statin use and mortality risks during the acute phase of ischemic stroke in patients admitted to an intensive care unit - Furlan, Natalia Eduarda; Souza, Juli Thomaz de [UNESP]; Zanati Bazan, Silmeia Garcia; Silva Franco, Roberto Jorge da; Luvizutto, Gustavo Jose; Gut, Ana Lucia; Modolo, Gabriel Pinheiro; Winckler, Fernanda Cristina; Martin, Luis Cuadrado; Bazan, Rodrigo (Assoc Arquivos Neuro- Psiquiatria, 2020)
Ischemic stroke is a common cause of death. The role of statins in the secondary prevention of the chronic ischemic stroke phase has been established. However, evidence regarding their efficacy in this phase is limited and contradictory. Objective: To evaluate the association between statin use and mortality risk during the acute phase of ischemic stroke in patients admitted to an intensive care unit. Methods: This was an observational and prospective study of ischemic stroke patients aged >= 18, admitted to an intensive care unit. Medications used during the first 7 days after the ictus, as well as medications used previously, were recorded. The primary outcome was all-cause mortality during the first 7 days. Results: We screened 212 patients and included 97 patients with ischemic stroke in the study period.The mortality rate among patients who used statins during the acute IS phase [14% (9/63)]was significantly lower than that among patients who did not use statins [41% (14/34); p=0.007]. This was confirmed in logistical regression with an 0.19 Odds Ratio - OR [p=0.018; 95% confidence interval - 95%CI 0.05-0.75]. Patients who died were older, had a higher incidence of acute myocardial infarction, higher scores on the NIHSS and lower systolic blood pressure. Statins and angiotensin converting enzyme inhibitors were used more frequently among survivors. These associations persisted even after adjustment for confounding variables. Conclusion: Statins and angiotensin converting enzyme inhibitors use during hospitalization were independently associated to a lower rate of all-cause mortality in the first 7 days of intensive care unit admission.
Keywords: stroke; statins; intensive care unit; mortality